Studies on the Growth Control of ZnO Nanostructures synthesized by the Chemical Method - Perillo,Patricia María (2018)
ABSTRACT ZnO nanostructures were synthesized through a chemical method using different Zn precursors and hexamethylenetetramine (HMTA) at 90 °C. The effects of the reactants on the morphological evolution of ZnO nanorods were investigated. The samples were characterized by using XRD, SEM, EDX and BET. The hexagonal wurtzite phase of ZnO was confirmed by X-ray diffraction (XRD). The performed analysis indicated that different morphologies were obtained by changing the reactants.